Effects of NSAIDs on the Release of Calcitonin Gene-Related Peptide and Prostaglandin E2 from Rat Trigeminal Ganglia. (25th October 2017) - Vellani, Vittorio; Moschetti, Giorgia; Franchi, Silvia; Giacomoni, Chiara; Sacerdote, Paola; Amodeo, Giada
Abstract : Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used to treat migraine, but the mechanisms of their effects in this pathology are not fully elucidated. The trigeminal ganglia and calcitonin gene-related peptide (CGRP) have been implicated in the pathophysiology of migraine. The release of CGRP and prostaglandin E2 (PGE2 ) from freshly isolated rat trigeminal ganglia was evaluated after oral administration of nimesulide, etoricoxib, and ketoprofen, NSAIDs with different pharmacological features. Thirty minutes after oral administration, nimesulide, 10 mg/Kg, decreased the GCRP release induced by an inflammatory soup, while the other NSAIDs were ineffective at this point in time. Two hours after oral nimesulide (5 and 10 mg/Kg) and ketoprofen (10 mg/Kg), but not of etoricoxib, a significant decrease in the CGRP release was observed. All drugs reduced PGE2, although with some differences in timing and doses, and the action on CGRP does not seem to be related to PGE2 inhibition. The reduction of CGRP release from rat trigeminal ganglia after nimesulide and ketoprofen may help to explain the mechanism of action of NSAIDs in migraine. Since at 30 minutes only nimesulide was effective in reducing CGRP release, these results suggest that this NSAID may exert a particularly rapid effect in patients with migraine.